First record of Seira dowlingi (Wray, 1953) (Collembola, Entomobryidae, Seirinae) from China and mitogenome comparison with the New World specimens - Godeiro, Nerivania Nunes; Zhang, Feng (Zootaxa, 2021)
Here, the first record of Seira dowlingi from Asia is reported and its newly generated mitogenome is compared with Neotropical specimens. Molecular analyses were performed based on low-coverage whole-genome sequencing and the complete mitogenome was assembled using NovoPlasty. Our results show that the Chinese specimens have the same color pattern, chaetotaxy, and almost identical mitogenomes, differing only on three nucleotides located in protein-coding genes. A maximum-likelihood phylogeny based on 13 mitochondrial genes was made and the specimens’ similarity was confirmed, as well as its phylogenetic position. Considering the large geographic distance between the American and the Asiatic populations, we believe that the presence of S. dowlingi in China is a result of anthropogenic introduction. The data generated here can be useful for further phylogeographic studies related to Seirinae subfamily or Collembola fauna in general.